Medical students’ career expectations and interest in opting for a surgical career (Swiss Medical Weekly, 2014)
BACKGROUND: Whilst surgery will face an imminent workforce shortage, an increasing majority of students decide against a surgical career. This study evaluated the current career expectations of medical students and tested a hands-on virtual reality (VR) intervention as a tool to increase their interest in surgery. METHODS: Randomly selected medical students of the University of Basel received a short questionnaire to rank their interest in five different postgraduate working environments prior to a lecture. After the lecture they participated in a hands-on VR demonstration. Thereafter an online questionnaire regarding workplace expectations, surgery and VR was sent to the students. RESULTS: The online questionnaire response rate was 87% (225/258). Before using the VR intervention, a nonsurgical career was preferred by the majority of students, followed by a surgical career, cross-disciplinary specialties, research and, finally, nonclinical work. Surgery (n = 99, 44%) and emergency medicine (n = 111, 49%) were rated as incompatible with a good work-life balance. Further drawbacks to surgery were apprehension of competitive mentality, unclear career perspectives and longer working hours. The VR intervention had limited impact on re-ranking the five working sectors and slightly increased the students’ interest in surgery. CONCLUSION: Students’ work environment expectations, their declining interest in a surgical career and the increasing need for surgeons represent challenges for surgical societies to address, in order to improve the attractiveness of surgery amongst students. VR sessions may be integrated as part of the actions required to improve students’ interest in a surgical career and should be further evaluated within controlled study designs.